Social behaviour in the non-breeding season in Great Tits Parus major and Willow Tits Poecile montanus: differences in juvenile birds’ route to territorial ownership, and pair-bond stability and mate protection in adults - Hogstad, Olav (Ornis Norvegica, 2015)
Great Tits Parus major and Willow Tits Poecile montanus are small passerine monogamous species that live in dominance-structured flocks outside the breeding season. Within such flocks, males dominate females, and within sex, adults generally dominate juveniles (first-year birds). However, whereas Willow Tits maintain a yearlong defence of large territories and their flocks have a constant membership, the Great Tits maintain looser organizations of their flocks that vary in size, and the birds move around irrespective of territorial ranges. I compared the aggressive behaviour between juvenile conspecifics of Great and Willow Tits from July through April during 2004–2014, and the intra-pair behaviour of adults during November–February in 2011−2014 in a subalpine forest in Budal, central Norway. Two maxima of aggressive interactions were found among juveniles of both species: one in August–September and one in March–April. For Great Tits the autumn-interactions were probably due to competition for food, whereas the spring-interactions reflected competition for territorial space. For Willow Tits, the interactions in August – September were caused by competition for flock membership and ownership for a territory in March–April. Because flock membership in general is the only possible way to territory ownership, also the aggressive behaviour among juvenile Willow Tits in autumn is most likely linked to territorial behaviour. I found three circumstances of immediate benefits of the pair bond for adult Willow Tits that are consistent with the hypothesis of mate protection and that differed from that of Great Tit pairs: Willow Tits had a shorter intra-pair distance, females received less aggression, and they had a higher foraging rate when accompanied by their mate than did females of Great Tit pairs. One out of the five Great Tit pairs studied became divorced, whereas the bonds of three Willow Tit pairs were stable over at least three to four years.